Hair Cortisol and Its Association With Psychological Risk Factors for Psychiatric Disorders: A Pilot Study in Adolescent Twins. (4th July 2016) - Rietschel, Liz; Streit, Fabian; Zhu, Gu; McAloney, Kerrie; Kirschbaum, Clemens; Frank, Josef; Hansell, Narelle K.; Wright, Margaret J.; McGrath, John J.; Witt, Stephanie H.; Rietschel, Marcella; Martin, Nicholas G.
Abstract : Measuring cortisol in hair is a promising method to assess long-term alterations of the biological stress response system, and hair cortisol concentrations (HCC) may be altered in psychiatric disorders and in subjects suffering from chronic stress. However, the pattern of associations between HCC, chronic stress and mental health require clarification. Our exploratory study: (1) assessed the association between HCC and perceived stress, symptoms of depression and neuroticism, and the trait extraversion (as a control variable); and (2) made use of the twin design to estimate the genetic and environmental covariance between the variables of interest. Hair samples from 109 (74 female) subjects (age range 12–21 years, mean 15.1) including 8 monozygotic (MZ) and 21 dizygotic (DZ) twin pairs were analyzed. Perceived stress was measured with the Perceived Stress Scale and/or the Daily Life and Stressors Scale, neuroticism, and extraversion with the NEO-Five Factor Inventory or the Junior Eysenck Personality Questionnaire, and depressive symptoms with the Somatic and Psychological Health Report. We found a modest positive association between HCC and the three risk factors — perceived stress, symptoms of depression, and neuroticism ( r = 0.22–0.33) — but no correlation with extraversion (-0.06). A median split revealed that the associations between HCC and risk factors were stronger (0.47–0.60) in those subjects with HCC >11.36 pg/mg. Furthermore, our results suggest that the genetic effects underlying HCC are largely shared with those that influence perceived stress, depressive symptoms, and neuroticism. These results of our proof of principle study warrant replication in a bigger sample but raise the interesting question of the direction of causation between these variables.